Analysis of the Impact of Substation Switching Operations on 5G Base Station Antenna Feeder Ports. Issue 1 (1st March 2022) - Wang, Zhihui; Liu, Shulei; Zhang, Ying; Hu, Yue; Zhu, Sicheng
Abstract: With the rapid development of the construction and application of 5G communication networks in the power grid, more and more 5G base stations need to be built in substations. 5G base stations have antennas placed outside in a complex electromagnetic environment, and they also become sensitive ports that induce external electromagnetic interference while sending and receiving signals. Especially the Electrical Fast Transient/Burst generated during the switch operation in the substation through the cable connecting the antenna and the base station equipment, at the antenna feeder port, generates electromagnetic disturbance that poses a potential threat to the operation of the equipment. This paper proposes an analysis method of an electromagnetic disturbance at the antenna feeder port of a 5G base station under the condition of switching operation of a substation. A 500kV substation is used to calculate the impact size, and the minimum distance between the antenna of the 5G base station and the switch operation device is determined. When the distance between the cable and the ground is two meters, the cable disturbance voltage reaches the maximum.